Animal restraint for veterinary professionals - Sheldon, C. C.; Sonsthagen, Teresa; Topel, James A. (Mosby Elsevier, 2006)
1 Restraint Principles 1 2 Knot Tying 7 3 Restraint of Cats 23 4 : Restraint of Dogs 53 5 Restrant of Cattle 105 Restra nt of Horses 127 S Restraint of Sheep 149 8 Restraint of Goats 159 9 Restrain of Swine 167 10 Restraint of Rodents, Rabbits, and Ferrets 177 11 Restraint of Birds 209